NGHIÊN CỨU ĐỘC TÍNH VÀ TÁC DỤNG HẠ GLUCOSE HUYẾT CỦA CAO CHIẾT LÁ CÂY LỘC VỪNG (Barringtonia acutangula) TRÊN CHUỘT ĐÁI THÁO ĐƯỜNG BẰNG STREPTOZOTOCIN - Nguyễn, Thị Ái Lan; Nguyễn, Phạm Tuấn (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
TOXICITY AND HYPOGLYCEMIC EFFECT OF Barringtonia acutangula LEAVES EXTRACT ON STREPTOZOTOCIN-INDUCED DIABETIC MICEStudies on toxicity and hypoglycemic effect of Barringtonia acutangula extract on diabetic mice by streptozotocin. The plant samples were extracted with solution ethanol 70% v/v. The acute toxicity was assessed in male and female Swiss albino mice by monitoring mortality and toxicity within 72 hours. The hypoglycemic effect was assessed in mouse model of hyperglycemia by streptozotocin at the dose of 150 mg/kg. The antidiabetic effect of extract of Barringtonia acutangula was compared with standard antidiabetic drug glibenclamid. The results of acute toxicity study showed that Barringtonia acutangula extract with the maximum dose on white mice was 50 g/kg body of mice with a mortality ratio of 0% after 72 hours. The extract of Barringtonia acutangula at dose of 125 mg/kg; 250 mg/kg and 500 mg/kg body of mice has the effect of reducing cholesterol, LDL-cholesterol and triglyceride levels. The extract of Barringtonia acutangula at dose of 125 mg/kg, 250 mg/kg and 500 mg/kg body of mice also has hyperglycemic effect on streptozotocin induced diabetic mice.